Case report: Different outcomes of two cases of relapsed/refractory T cell acute lymphoblastic leukemia treated with anti-CD7 chimeric antigen receptor T cells bridging to allogeneic hematopoietic stem cell transplantation: from curative promise to fatal risk - Pan, Zhijuan; Guo, Yanru; Zhang, Ying; Chang, Shuting; Sun, Jiajia; Guo, Zhiping; Zhang, Yiqun (Frontiers in Oncology, 2026)
Consolidative allogeneic hematopoietic stem cell transplantation (allo-HSCT) after chimeric antigen receptor (CAR) T-cell therapy is an emerging modality in hematologic malignancies. Knowledge regarding the optimal interval and pretreatment regimen between CAR T-cell therapy and allo-HSCT remains limited. Here, we report two cases of confirmed relapsed/refractory (R/R) T-cell acute lymphoblastic leukemia (T-ALL) treated with autologous anti-CD7 CAR T cells infusion bridging to allo-HSCT. Case 1 had a poor prognosis due to grade 3 cytokine release syndrome (CRS), infection, drug-related organ toxicity, hyperacute graft-versus-host disease (GVHD), and transplant-associated thrombotic microangiopathy (TA-TMA). In contrast, case 2 demonstrated a favorable course, marked by effective inflammation control, complete recovery following CAR T-cell therapy, and timely transplantation. These cases indicate that anti-CD7 CAR T-cell therapy represents a promising therapeutic strategy for R/R T-ALL. However, its integration with allo-HSCT constitutes a high-risk clinical approach that requires careful and individualized management.